Magnetic Signatures of Large-Scale Electric Currents in the Earth’s Environment at Middle and Low Latitudes - Christine Amory-Mazaudier (Atmosphere, 2022)
The purpose of space weather is the systemic study of the Sun–Earth system, in order to determine the impact of solar events on the electromagnetic environment of the Earth. This article proposes a new transdisciplinary approach of the Sun–Earth system based on the universal physical process of the dynamo. The dynamo process is based on two important parameters of the different plasmas of the Sun–Earth system, the motion and the magnetic field. There are four permanent dynamos in the Sun–Earth system: the solar dynamo, the Earth dynamo, the solar wind-magnetosphere dynamo, and the ionospheric dynamo. These four permanent dynamos are part of different scientific disciplines. This transdisciplinary approach links all of these dynamos in order to understand the variations in the Earth’s magnetic field. During a magnetic disturbed period, other dynamos exist. We focused on the ionospheric disturbed dynamo generated by Joule energy dissipated in the high latitude ionosphere during magnetic storms. Joule heating disrupts the circulation of thermospheric winds and in turn generates disturbances in the Earth’s magnetic field. This systemic approach makes it possible to understand magnetic disturbances previously not well understood.